THE INFLUENCE OF STEEL FIBRES AND RPC THICKNESS ON THE BEHAVIOUR OF HYBRID COLUMNS UNDER CONCENTRIC LOADING - Ali Yassin, Layla; hussein mohammed, Alyaa; Rauf, Farah (Journal of Applied Engineering Science, 2022)
In this paper a test was performed on six reinforced concrete rectangular columns subjected to concentric loading up to failure. The material used in this investigation included normal concrete, NC, and reactive powder concrete, RPC. Two columns were cast as control specimens with NC and RPC. The remaining four were of hybrid combination having the NC in the centre and the RPC surrounded it. Variables investigated were the effect of steel fibre volumetric ratio, Vf, (0.5, 1 and 1.5) as well as the thickness of the external RPC part, (40 and 20) mm. The columns were of rectangular section having the dimensions of (100×200×740) mm.Data recorded included: crack and ultimate loads as well as the longitudinal and lateral strains. Experimental results indicated that the behaviour of the hybrid reinforced concrete columns were approaching that of the full RPC.
Keywords: hybrid concrete, normal concrete, reactive powder concrete, short columns, steel fibres, concentric loading, rectangular section